Differences in Influencing Factors Between Non-suicidal Self-Injury and Suicide Attempts in Chinese Adolescents: The Role of Gender - Xu, Huiqiong; Jiang, Zhicheng; Li, Shuqin; Zhang, Xinyu; Xu, Shaojun; Wan, Yuhui; Tao, Fangbiao (Frontiers in Psychiatry, 2022)
Abstract Introduction Non-suicidal self-injury (NSSI) and suicide attempts (SA) are common in adolescents and are important risk factors for suicide deaths. They are related to various psychosocial, behavioral, and biological factors. We aimed to compare the differences on psychological behavior problem and family environment characteristics between NSSI and SA, and the role of gender. Methods A multi-center population-based survey was conducted in 29 schools across 4 provinces in China. A total of 14,500 urban and rural adolescents in grades 7–12 completed a structured questionnaire to report their sociodemographic information, psychological and behavioral characteristics, childhood maltreatment, parent-child relationships, NSSI, and SA. Post hoc tests, pairwise comparisons, and multinomial logistic regression analyses were conducted to explore the differences and similarities between subjects who had engaged in NSSI and SA. Results The prevalence of NSSI and SA were 27.3% and 4.9%, respectively, and the co-occurrence of these two behaviors (NSSI + SA) was reported to 2.8%. The NSSI + SA group scored the highest on all study variables, followed by the SA-only group, the NSSI-only group, and the non-self-harm (NSH) group (p < 0.001). Compared with the NSH group, adolescents who reported either NSSI or SA scored significantly higher on all study variables (p< 0.0083). The comparison between other self-harm groups, this difference have varied in all research variables. Conclusion The current study indicate that psychological, behavioral, and family relationships profiles of Chinese adolescents with SA and NSSI are similar, but the measured problematic characteristics were more severe in suicide attempters. In the future, it’s necessary to pay more attention to adolescents with more serious psychological and behavioral problems to prevent and early intervene in their self-harm, and actively explore gender differences.